The Correlations Between Parental Patterns and Family Income with The Incident of Wasting in Toddlers Aged 12-59 Months - Lenny; Nurhamidi; Syainah, Ermina; Aprianti (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
Child malnutrition is a crucial public health problem worldwide. Parenting style plays a significant role in children's nutritional status, particularly in meeting their nutritional needs. Low-income families tend to have limited access to nutritious food, increasing the risk of malnutrition. The aim of this study was to analyze the relationship between parenting patterns and family income with the incidence of malnutrition in toddlers aged 12-59 months in the working area of ​​the Sungai Turak Public Health Center. This research is an analytical observational study with a cross-sectional design and quantitative methods. This research was conducted in the Sungai Turak Public Health Center from August to December 2025. The study population was 826 toddlers. The sample was taken using Proportionate Stratified Random Sampling with 99 respondents. Data analysis used the chi-square test. The incidence of malnutrition in toddlers was 43 people (43.4%). 8 people (8.1%) had poor parenting patterns. 88 people (88.9%) had family incomes below the minimum wage (UMK) of Rp. 3,496,195. There was a correlations between maternal parenting patterns (p=0.020, PR=10.694), family income (p=0.021, PR=9.130) and the incidence of malnutrition in toddlers aged 12-59 months. There is a correlations between parenting style and family income and malnutrition in toddlers aged 12-59 months in the working area of the Sungai Turak Public Health Center. Parents are encouraged to increase their knowledge about nutritional issues that can affect toddlers and the long-term impact of malnutrition.